Evaluasi Program Penataan Koridor Kalireyeng di Kelurahan Kebondalem Kecamatan Kendal Kabupaten Kendal - Silvia Nerisa Fortuna; Parfi Khadiyanta (Jurusan Perencanaan Wilayah dan Kota, 2019)
The rise of residential development that does not comply with the designation of land also occurred in Kebondalem precisely in the right trompo border irrigation or known by the public as Kalireyeng. People use river border area as a place to stay. The lack of public understanding about sanitation and waste contributed to the degradation neighborhoods and appear dirty and unhealthy. In 2008, Kebondalem become one of the pilot project locations of Neighborhood Development. BKM with the community has been carrying out development planning process in a participatory neighborhoods. Kalireyeng Corridor Planning Program is expected to resolve the settlement issue as complex as previously described. However, there were indications that the implementation of the program has not been optimal. This study aims to evaluate the level achievement of program. The evaluation criteria are effective, relevant, and responsiveness. The analytical method used in this research is quantitative descriptive analysis and scoring. The data used in this analysis comes from the study of documents, observation, and questionnaires. After the analysis, it is known that the level of achievement of program is effective (a score of 30.9 to 36.4) with a score of 36, relevant (score of 30.9 to 36.4 ) with a score of 32, responsiveness (a score of 39.7 to 46.8) with a score of 42. Thus, the level of achievement of the program included in the category managed by 79.8%.